Fresh Osteochondral Allograft Transplantation in Osteochondritis Dissecans in the Knee Joint - Tommaso Roberti di Sarsina; Michele Fiore; Vito Coco; Marco Govoni; Leonardo Vivarelli; Nicola Rani; Nicolandrea Del Piccolo; Dante Dallari (Life, 2021)
Osteochondritis dissecans (OCD) is a chronic and painful joint condition that can occur from childhood through to adult life. Microtrauma, vascular insufficiency, or abnormal endochondral ossification are the most common causes of OCD. Reconstructive techniques for OCD of the knee are typically necessary when either non-operative or reparative/regenerative operative treatments fail, or when the OCD is irreversible. To analyze the clinical outcomes and failure rates of fresh osteochondral allograft transplantation (FOCA) used as a reconstructive strategy in OCD patients, an in-depth search was carried out on the PubMed, Scopus, and Web of Science databases concerning the existing evidence related to the use of FOCA for OCD patients in the knee joint. A total of 646 studies were found through the search and 2 studies were added after a cross-referenced examination of the articles within the bibliography. Six studies with a total of 303 OCD lesions treated with FOCA, with a mean follow-up of 6.3 years, were included. Although a limited number of low-level evidence studies on this topic are available in previous research, satisfactory clinical results and survival rates of the reconstruction are reported. However, to better define the real advantages of FOCA in the healing process of OCD lesions, comparative studies with different techniques are needed.